The Effect on the Information Quality of Mobile Advertising on Brand Attitudes and Purchase Intention in Instagram - Egan Evanzha Yudha Amriel (Journal of Economics, Business, and Government Challenges, 2018)
In this study, social media Instagram is an application to share the photos and video that is currently widely used for culinary business purposes accessible in the mobile channel. This study aims to determine the effect on the information quality of mobile advertising on brand attitudes and purchase intention. Media research used a third party, namely the culinary @wenaktok in displaying advertisinginformation of a food product because the third party has a better effect in advertising rather than a corporate account. The approach used in this study is the quantitative approach. Type sampling technique of non-probability sampling in this study was convenience sampling.Respondents in this study were 152 respondents who are users of Instagram. Analysis technique used in this study isPartial Least Squares (PLS). This study has shown that the information quality of mobile advertisinghas a significant influence on ads attitudes, brand attitude, and purchase intention. The ads attitude has a significant influence on purchase intentions and brand attitudes. The brand attitude has an influence on consumers' purchasing intentions.The conclusion was that the information quality of mobile advertising in @wenaktok account has a significant influence on the ads attitudes, brand attitudes, and purchase intentions of consumers in food products advertised on social media Instagram through culinary account. So that @wenaktok culinary accounts has information quality mobile advertising that is good to used to advertise in Instagram.